2016
DOI: 10.1007/s11655-016-2737-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive treatment with Chinese medicine in patients with advanced non-small cell lung cancer: A multicenter, prospective, cohort study

Abstract: Additional CM may prolong survival and improve the QOL patients with NSCLC. The adverse effects of radio- and chemotherapy may be attenuated as CM is used in combination with conventional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…You et al have uncovered that a Chinese Herbal Medicine Baicalin represses cell proliferation, migration, invasion, and induces cell apoptosis in NSCLC cells 22. Liu et al have found that treatment with Chinese Medicine may prolong the survival rate of NSCLC patients 23. The anti-tumor effect of Cordyceps militaris was associated with an induction of cell cycle arrest and mitochondrial-mediated apoptosis 24.…”
Section: Discussionmentioning
confidence: 99%
“…You et al have uncovered that a Chinese Herbal Medicine Baicalin represses cell proliferation, migration, invasion, and induces cell apoptosis in NSCLC cells 22. Liu et al have found that treatment with Chinese Medicine may prolong the survival rate of NSCLC patients 23. The anti-tumor effect of Cordyceps militaris was associated with an induction of cell cycle arrest and mitochondrial-mediated apoptosis 24.…”
Section: Discussionmentioning
confidence: 99%
“…[2022] A prospective cohort study involving patients with advanced NSCLC revealed that the median survival was prolonged in the group treated with integrated traditional Chinese medicine (TCM) and CCT compared to the CCT-alone group (16.60 vs 13.13 months, P < .01). [23] A meta-analysis demonstrated that concurrent administration of TCM herbs plus EGFR tyrosine kinase inhibitor (EGFR-TKI) resulted in a significantly better response rate, as well as 1- and 2-year survival rates, compared to EGFR-TKI alone in patients with advanced NSCLC. [24] In a randomized controlled trial involving patients with stage IIIB and IV NSCLC, intravenous pharmacopuncture (Cinobufacini injection), oral herbal decoction, and acupoint application (mono-TCM treatments) for 21 days were shown to have times to progression and OSs similar to those of patients treated with chemotherapy alone and higher 1-year survival rate (78.1% vs 53.1%, P = .035).…”
Section: Discussionmentioning
confidence: 99%
“…Good-quality English-language published trials in this area are rare. Liu et al [44] reported a RCT of 474 stage IIIeIV non-small cell lung cancer (NSCLC) patients and compared the outcome of additional Chinese herbal medicine (IM group) with the standard therapy (radiotherapy, chemotherapy and optimal supportive therapy according to NCCN guidelines) to standard therapy alone (WM group). The median overall survival was 16.60 and 13.13 months in the IM and WM groups, respectively (P < 0.01).…”
Section: Herbal Medicine Decoctionmentioning
confidence: 99%